(untitled) (Neo Scientific Peer Reviewed Journal, 2026)
This article first published in 2025 held Bukhara Biennale content , goals and practical importance scientific analysis does . In the study biennial historical city in the context place , modern art and traditional handicraft harmony , as well as Bukhara for tourism , cultural diplomacy and creative economy development added contribution illuminated . " Recipes for Broken Hearts" hearts for recipes ) concept based on organization done biennial conceptual approach , creative criteria and social importance of analysis will be done.